Influence of the oxygen partial pressure on the growth and optical properties of RF-sputtered anatase TiO2 thin films - Korpi, A.R. Grayeli; Rezaee, Sahare; Luna Criado, Carlos; Talu, S.; Arman, A.; Ahmadpourian, Azin (2017)
Titanium dioxide (TiO2) films with thicknesses around 300 nm were deposited on glass substrates by reactive radio frequency (RF) magnetron sputtering at constant RF sputtering power (200 W), high sputtering pressure and room temperature. The effects of the oxygen presence on the growth and properties of the films were investigated using mixtures of Ar and O2 with different O2/(Ar + O2) ratios (from 0.0 to 0.3) during the sample deposition. The crystalline properties and surface morphology were characterized using X-ray diffraction (XRD) and atomic force microscopy (AFM), respectively. The optical properties were studied by ultraviolet–visible–near infrared (UV–Vis–NIR) spectroscopy, and the refractive index and the thickness of the samples were obtained using the Swanepoel method. The obtained results indicate that all the TiO2 films grew with an anatase phase and with an improved crystallinity at O2/(Ar + O2) = 0.2. However, AFM studies show that the grain size and surface roughness decrease as the O2/(Ar + O2) ratio increases from 0.0 to 0.3. Moreover, a maximum refractive index was obtained for the sample prepared at O2/(Ar + O2) = 0.2.